Care of the adult patient with cystic fibrosis. - Aronson, Barbara S; Marquis, Melissa (Medsurg nursing : official journal of the Academy of Medical-Surgical Nurses, 2004)
Recently published consensus statements and conference proceedings from the Cystic Fibrosis Foundation provide new direction with regard to the etiology, diagnosis, and treatment of the adult patient with cystic fibrosis (CF). Survival has improved through early diagnosis and improved treatment, and aggressive management of complications. The current state of knowledge, the most recent evidence-based treatment options, and essentials of nursing care for the adult patient with CF are outlined.
Keywords: *Cystic Fibrosis/th [Therapy]; Adult; Age Factors; Cystic Fibrosis; Cystic Fibrosis/di [Diagnosis]; Cystic Fibrosis/ep [Epidemiology]; Cystic Fibrosis/et [Etiology]; Diabetes Mellitus; Diabetes Mellitus/et [Etiology]; Diabetes Mellitus/pc [Prevention & Control]; Female; Gastrointestinal Diseases; Gastrointestinal Diseases/et [Etiology]; Gastrointestinal Diseases/pc [Prevention & Control]; Genetic Predisposition to Disease; Genetic Predisposition to Disease/ge [Genetics]; Humans; Infection Control; Infection Control/mt [Methods]; Longevity; Nurse's Role; Phenotype; Reproductive Medicine; Reproductive Medicine/mt [Methods]; Respiratory Therapy; Respiratory Therapy/mt [Methods]; Respiratory Tract Infections; Respiratory Tract Infections/et [Etiology]; Respiratory Tract Infections/pc [Prevention & Control]; Terminal Care; Terminal Care/mt [Methods]; adult; age; artificial ventilation; case report; cystic fibrosis; dept.nur; diabetes mellitus; female; gastrointestinal disease; genetic predisposition; genetics; human; infection control; longevity; methodology; nurse attitude; phenotype; reproduction; respiratory tract infection; review; terminal care; ⛔ No DOI found

Family rituals that provide meaning for single-parent families: - Moriarty, Patricia Hale; Wagner, Linda D (Journal of Family Nursing, 2004)
The number of single-parent families has increased dramatically in the United States. The purpose of this study was to explore the types of family rituals present in single-parent families and their meaning within the family context. Little is known about family rituals in single-parent families, and therefore grounded theory was the qualitative research method used for this study. Unstructured face-to-face interviews were used to obtain data from a theoretical sample of seven single parents. Data analysis appropriate to the grounded theory method was utilized to identify a core variable and an emerging theory. Six types of rituals: connection, spiritual, love, recreation, celebration, and evolving were found to be used by these single-parent families as a way to facilitate family cohesion and instill family values. Applicability of the findings of this study are beneficial for nurses working with clients with diverse, changing, and complex social situations such as the single-parent family. © 2004 Sage Publications.
Keywords: Family health; Qualitative research; Rituals; Single-parent family; dept.nur